Clinical significance of measuring the lateral atlantodental interval in children with tic disorders - Peng, Beiru; Peng, Runxin; Chen, Xiumei; Lu, Xuanrui; Huang, Chuyu; Zhang, Lijiao; Liang, Gaofeng (Frontiers in Neurology, 2025)
BackgroundThe pathophysiology and causation of tic disorders (TD) remain unclear. Clinically, children with TD with head and neck tics, trunk tics, often showing associated spinal abnormalities, may be closely related to the atlantoaxial joint. The purpose of this research is to assess the level of lateral atlantodental interval (LADI) in children with TD and to explore the correlation between TD and the asymmetry of bilateral LADI.MethodsThe variance in the bilateral lateral atlantodental interval (VBLADI) level was investigated in a retrospective analysis of 80 children with TD between July 2021 and December 2024. Meanwhile, examining the correlation between tic symptoms and VBLADI levels based on VBLADI ≤ 2 mm and >2 mm for grouping.ResultsThe mean VBLADI among children with TD was 1.32 mm (range: 0.62–2.19 mm). A robust and statistically significant association was identified between head shaking and VBLADI >2.2 mm, even after adjusting for potential confounders and correcting for multiple comparisons [adjusted odds ratio (aOR) = 12.64; FDR q-value = 0.035). However, no linear correlation was observed between VBLADI levels and the total Yale Global Tic Severity Scale score (p = 0.780).ConclusionsAsymmetry in the bilateral LADI is associated with TD symptoms, particularly head shaking. Nonetheless, VBLADI levels do not correlate with the overall severity of TD.